"You must first save her life": community perceptions towards induced abortion and post-abortion care in North and South Kivu, Democratic Republic of the Congo. Issue 1 (1st January 2019) - Casey, Sara E; Steven, Victoria J; Deitch, Julianne; Dumas, Erin Files; Gallagher, Meghan C; Martinez, Stephanie; Morris, Catherine N; Rafanoharana, Raoza Vololona; Wheeler, Erin
ABSTRACT: Structural barriers such as a restrictive legal environment, limited medical resources, and high-costs inhibit access to safe abortion in the Democratic Republic of the Congo (DRC); these barriers are exacerbated by two decades of conflict. Socio-normative barriers further complicate access to safe abortion and post-abortion care (PAC) in DRC, where fear of abortion-related stigma may lead women to avoid PAC services. Programme partners support the Ministry of Health to provide good quality contraceptive and PAC services in North and South Kivu, DRC. This paper presents results from focus group discussions that explored community members' attitudes towards women who induce abortion and their care-seeking behaviour in programme areas. Results indicate that while abortion stigma was widespread, community members' attitudes towards women who induced abortions were not one-dimensional. Although they initially expressed negative opinions regarding women who induced abortion, beliefs became more nuanced as discussion shifted to the specific situations that could motivate a woman to do so. For example, many considered it understandable that a woman would induce abortion after rape: perhaps unsurprising, given the prevalence of conflict-related sexual violence in this area. While community members believed that fear of stigma or associated negative social consequences dissuaded women from seeking PAC, a majority believed that all women should have access to life-saving PAC. This commitment to ensuring that women who induced abortion have access to PAC, in addition to the professed acceptability of induced abortion in certain situations, indicates that there could be an opening to destigmatise abortion access in this context.